Dupuytren's contracture in manual workers. Issue 1 (February 1982) - Bennett, B
Abstract : The incidence of Dupuytren's contracture in a polyvinyl chloride (PVC) manufacturing plant, where a great deal of bagging and packing took place by hand, was higher than in another plant in which there was no bagging or packing. The incidence in the packing plant was double that found in an earlier survey by Early at Crewe Locomotive Works of 4801 individuals, most of whom were manual workers. The implication is that the nature of the work of bagging and packing in our PVC compounding plant may have triggered Dupuytren's contracture.